Factors that affect the willingness of the people to avail informal credit. - Siwala, Jacqueline S (2003.)
The ubiquity of informal lending transaction in the Philippines is not a laughing matter. These credit transactions are sourced out from lenders not regulated, and therfore, not taxed by the government . Hence, these transactions are part of the country's so-called "underground economy". Despite the negative impression on informal credit, however this type of credit florish even in the remote areas of the country. (p)This is a descriptive study on the factors that affect the willingness of the people to avail informal credit with the following objectives: (1) to know if the socio-economic-demographic status of the people affect their willingness to avail informal credit; (2) to know if the level of awareness on informal credit affects the willingness of the people to avail such credit; and lastly, (3) to know if the prevailing lending practices in their community affect the people's willingness to avail informal credit. The study was conducted at Brgy. Rizal Palapala Zone II near the Iloilo South Terminal or which is commonly known as "Super". The respondents are the bona fide residents of the said barangay and are of ages eighteen years old and above. Survey informants are the methods employed in the study with interview schedules as the instrument. (p)The results show that the people's socio-economic and demographic status with indicators like age, occupation, civil status, educational attainment, household size, and household income and expenditure per month affect their willingness to avail informal credit. Gender, however, does not affect the people's willingness to avail informal credit. The level of awareness on informal credit and the prevalent lending practices also affect their willingness to avail such credit. With "five-six" lenders, "lending", and friends and relatives as the most frequent sources of informal credit.
Thesis (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Credits, Informal